Business Survival and Success of Young Small Business Owners - C. Mirjam van Praag (Tinbergen Institute, 2003)
Little empirical evidence provides insight in person-oriented drivers of business survival and success of small business owners. In this paper I perform a duration analysis of business survival amongst young white (selfemployed) small business owners in the U.S. Compulsory exits are distinguished from voluntary exits. This enables an alternative definition of business success: the longer one can survive and prevent involuntary exit, the more successful one is. Potential drivers of survival are derived from recent empirical evidence in related studies. The potential drivers of success are also derived from historical economic thinkers such as Marshall and Schumpeter. The estimated hazard rates are affected by characteristics of the small business owner and business conditions.
Keywords: C41; G33; J23; M13; 330; self-employment; entrepreneurship; business survival; small business; and success.; Selbstständige; KMU; Unternehmenserfolg; USA